UPAYA PENERAPAN GERAKAN LITERASI SEKOLAH DI AWAL PEMBELAJARAN UNTUK MENINGKATKAN MINAT BACA SISWA KELAS 5 DI SDN MOJOAGUNG 01 PATI - Lisofa Intan Khoirunisa; Sunan Baedowi; Lina Putriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of the study is based on the low interest in reading among students, Saptadi Ismanto Heri, Husni Wahyudin, Sunan Baedowi (2023) stated that education is a basic need for every human being born in the world. Sutinah, Putriyanti Lina (2024) stated that literacy is an essential skill for theintellectual and social development of individuals. This study aims to determine the application of GLS reading interest in 5th grade students of SDN MOJOAGUNG 01 PATI. The research method used is qualitative with pretest-posttest. The research population was 28 5th grade students of SDN Mojoagung 01. The instruments used in this study include observation, pretest-posttest, interviews to determine the effectiveness of increasing reading interest. The results of the study showed that there was an increase in the average value from the pretest to the posttest with a KKM of 75. In addition,reading motivation showed positive results with an average of 78.89% of students being in the category of meeting the KKM limit applied in schools. The conclusion of this study is that the application of GLS at the beginning of learning can improve the reading interest of 5th grade students at SDN MOJOAGUNG 01 PATI.